(untitled) (Research, Society and Development, 2024)
Introduction: The literature points out that nutritional management is pointed out as a facilitator to improve the signs and symptoms of the disease, as well as to prevent correlated pathologies. Objective: The present study aims to evaluate the influence of diet on the treatment of polycystic ovary syndrome. Methodology: The search for articles was carried out in the database: Pubmed, published between the years 2019 and 2024, using the descriptors "polycystic ovary syndrome", "diet" and "treatment". 48 articles were found and 16 were used. Results: The main diets analyzed were the low glycemic index diet, a low-caloric diet rich in protein, in addition to the supplementation of pomegranate juice in the form of a symbiotic, turmeric, coenzyme Q10 and fennel. Conclusion: Although there is evidence that there is a correlation between diet and the treatment of PCOS, more studies are needed to trace the complete mechanism between these two conditions.